2005
DOI: 10.1038/sj.embor.7400516
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pestis kills Caenorhabditis elegans by a biofilm‐independent process that involves novel virulence factors

Abstract: It is known that Yersinia pestis kills Caenorhabditis elegans by a biofilm-dependent mechanism that is similar to the mechanism used by the pathogen to block food intake in the flea vector. Using Y. pestis KIM5, which lacks the genes that are required for biofilm formation, we show that Y. pestis can kill C. elegans by a biofilm-independent mechanism that correlates with the accumulation of the pathogen in the intestine. We used this novel Y. pestis-C. elegans pathogenesis system to show that previously known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…Several genes of P. aeruginosa, S. aureus, S. marcescens, and Yersinia pestis have been newly identified and found to be involved in the pathogenicity of C. elegans, and some have also been found to be essential for virulence in the mammalian system 4,14,29,33) . However, the bacterial pathogenicity observed in C. elegans models may reflect other virulence-related aspects rather than enteropathogenicity; although the current observations do not necessarily exclude the possibility that the characteristics associated with nematocidal activity may be prerequisites for some human enteropathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes of P. aeruginosa, S. aureus, S. marcescens, and Yersinia pestis have been newly identified and found to be involved in the pathogenicity of C. elegans, and some have also been found to be essential for virulence in the mammalian system 4,14,29,33) . However, the bacterial pathogenicity observed in C. elegans models may reflect other virulence-related aspects rather than enteropathogenicity; although the current observations do not necessarily exclude the possibility that the characteristics associated with nematocidal activity may be prerequisites for some human enteropathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of C. elegans was accomplished by transferring nematodes, propagated on E. coli OP50, onto bacterial lawns of Y. pestis KIM5. In previous studies, we have demonstrated that following ingestion Y. pestis establishes a persistent infection in the C. elegans intestine (8). Even though C. elegans is not known to be a natural host for Y. pestis, this persistent colonization of the nematode intestine by Y. pestis allows the host to properly recognize and respond to pathogen infection.…”
Section: Identification Of Inducible Immune Responses To Y Pestismentioning
confidence: 96%
“…Once in the gut, however, pathogenic bacteria can overcome innate immune responses to proliferate and kill C. elegans. Infection of C. elegans with Y. pestis KIM5 leads to a persistent and lethal colonization of the nematode intestine (8). In addition, similar virulence factors are required for pathogenicity in nematodes and mice (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type and arr-1(ok401) animals exhibited similar pumping rates on P. aeruginosa, indicating that they are exposed to a comparable dose of pathogen (data not shown). To determine whether the enhanced immune response caused by mutation in the arr-1 gene is specific to P. aeruginosa, we exposed arr-1(ok401) animals to S. enterica and Y. pestis, two Gram-negative pathogens known to kill C. elegans (24,25). As shown in Fig.…”
Section: Arr-1 Signaling Regulates Pathogen Resistance and Lifespanmentioning
confidence: 99%